The Issues of Training and Changing Attitudes Towards/for Physical and Sports Activities - RUSU, Oana (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Attitudes determine how the individual acts towards others and towards different social events, feelings, behaviors and choices becoming predictors of behavior. The sources of attitude formation are social learning, social comparison and genetic inheritance, these functioning as very influential cognitive patterns. Often, attitude establishes behavior, but there are also situations in which there are gaps between them. Knowledge and awareness of the effects of physical and sports activities, in correlation with different demographic and psycho-social variables, constitute the premises for the formation and change of the individual’s attitudes. Favorable attitudes towards (practicing) physical and sports activities are positively associated with behavioral intentions in different contexts (within the school curriculum in physical education classes, in an autonomous regime, in free time, in sports clubs and associations specific to certain sports branches, etc.), producing effects on the individual, but also at the level of the community to which he belongs. Sometimes sports contexts, especially those associated with high-performance sports, can also cause negative attitudes with negative influences on the personality, behavior and mental health of the individual (athlete, coach). The attitudinal changes towards (the practice of) physical and sports activities are the result of a dynamic, staged process, sometimes assisted by specialized personnel, the effects of the change occurring at the cognitive and affective level, and, subsequently, at the psychomotor level, of action. The processes of training and attitudinal change towards practicing physical and sports activities, including performance sports, can vary throughout life. Problematicile formării și schimbării atitudinilor față de/ pentru practicarea activităților fizice și sportive. Atitudinile determină modul în care individul acționează față de ceilalți și față de diferite evenimente sociale, sentimentele, comportamentele și alegerile devenind predictori ai comportamentului. Sursele formării atitudinilor sunt învățarea socială, compararea socială și moștenirea genetică, acestea funcționând ca niște tipare cognitive foarte influente. Adesea, atitudinea întemeiază comportamentul, dar există și situații în care există decalaje între acestea. Cunoașterea și conștientizarea efectelor activităților fizice și sportive, în corelație cu diferite variabile demografice și psiho-sociale, constituie premisele formării și schimbării atitudinilor individului. Atitudinile favorabile față de (practicarea) activităților fizice și sportive sunt asociate pozitiv cu intențiile comportamentale în contexte diferite (în cadrul curriculei școlare la orele de educație fizică, în regim autonom, în timpul liber, în cluburi și asociații sportive specifice unor ramuri sportive etc.), producând efecte asupra individului, dar și la nivelul comunității din care face parte. Uneori, contextele sportive, în special cele asociate sportului de înaltă performanță, pot determina și atitudini negative cu influențe negative asupra personalității, comportamentului și a sănătății mentale a individului (sportiv, antrenor). Schimbările atitudinale față de (practicarea) activităților fizice și sportive reprezintă rezultatul unui proces dinamic, etapizat, uneori asistat de personal specializat, efectele schimbării producându-se la nivel cognitiv și afectiv, și, ulterior, la nivel de psihomotor, de acțiune. Procesele de formare și schimbare atitudinale față de practicarea activităților și fizice si sportive, inclusiv a sportului de performanță, pot varia pe tot parcursul vieții. Cuvinte-cheie: atitudini, activitate fizică, sport, sănatate mentală Received 2024 November 25; Revised 2025 January 20; Accepted 2025 January 24; Available online 2025.02.10; Available print 2025.02.28